2018
DOI: 10.1051/epjconf/201817305003
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Vesicular Systems Parameters: Parallel Implementation and Analysis of the PTNS Vesicle Structure

Abstract: Abstract. Parameters of the phospholipid vesicular systems are determined by means of minimization of the discrepancy between experimental data on the small angle scattering intensity and the numerical results within the frame of the separated form factors method. Effectiveness of parallel implementation is tested at the cluster HybriLIT. Results of numerical analysis of small angle neutron scattering data on polydispersed population of unilamellar vesicles of phospholipid transport nanosystem are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…In the photo, one can see discrete particles that are predominantly spherical and/or rod-shaped. Previously, a combination of two methods-small-angle neutron scattering in the range of PhTNS concentration in heavy water of 5-25% by weight and small-angle scattering of X-ray synchrotron radiation in several concentrations in water-was used to determine the single-layer vesicular structure of phospholipid transport nanosystem (PhTNS) [23,24]. It was found that the size of vesicles decreased with an increase in the maltose concentration and was about 27.2 + 0.2 nm at a concentration of 20%.…”
Section: Transmission Electron Microscopymentioning
confidence: 99%
“…In the photo, one can see discrete particles that are predominantly spherical and/or rod-shaped. Previously, a combination of two methods-small-angle neutron scattering in the range of PhTNS concentration in heavy water of 5-25% by weight and small-angle scattering of X-ray synchrotron radiation in several concentrations in water-was used to determine the single-layer vesicular structure of phospholipid transport nanosystem (PhTNS) [23,24]. It was found that the size of vesicles decreased with an increase in the maltose concentration and was about 27.2 + 0.2 nm at a concentration of 20%.…”
Section: Transmission Electron Microscopymentioning
confidence: 99%